WTO dispute settlement : one-page case summaries 1995-September 2006 (WTO GenevaCH, 2006)
Summarizes the core facts and substantive findings contained in the adopted panel and, where applicable, Appellate Body reports for each decided case. Where relevant, also summarizes key findings on significant procedural matters.
Keywords: DISPUTE SETTLEMENT